Fred Lorey Passed Away - Lisa Feuchtbaum; Michele A. Lloyd-Puryear (International Journal of Neonatal Screening, 2020)
To tackle the ever-increasing ambitions of the International Journal of Neonatal Screening (IJNS), in November 2019, we were looking for an Associate Editor to strengthen the Editorial board of IJNS [...]